Pembuatan Minuman Kombucha dengan Mengkaji Perbandingan Bunga Telang dengan Sari Buah Nanas dan Konsentrasi Starter Scoby - Chairil Anwar; Irhami Irhami; Ika Rezvani Aprita (Agriculture Faculty, 2025)
Kombucha bunga telang drink is a fermented drink that can be categorized as a functional drink and has many benefits that greatly play a role in boosting the immune system. This study aims to determine the concentration of SCOBY starter culture and the ratio between the solution of telang flower and pineapple juice added to the functional drink of telang flower kombucha. This research was carried out in a laboratory with a Complete Random Design (RAL) research design with two factors studied. The first factor was the ratio between the solution of telang flower and pineapple fruit extract (85:15; 75:25; and 65:35) while the second factor studied was the concentration of SCOBY stater which consists of 3 (three) levels, namely: 5%, 10%, and 15%. The results showed that the comparison treatment of telang flowers with pineapple juice had a very real influence on the pH value, organoleptic aroma, taste, and color of kombucha drinks. The concentration of SCOBY starter culture had a very real effect on pH and organoleptic taste but had no real effect on aroma and color. The interaction between the ratio of telang flowers to pineapple juice and the concentration of SCOBY starter culture had a real effect on the organoleptic aroma and taste but had no real effect on the pH and color of kombucha tea. From the study, it can be concluded that kombucha tea with the best organoleptic quality was obtained by comparing telang flowers with pineapple juice 85:15 and a starter culture concentration of 5% SCOBY (N1S1) with product characteristics: pH 2.55; aroma score 3.61; taste score 3.91; and a color score of 4.07.